Sunk time fallacy with recoverable monetary costs. Issue 2 (7th March 2019) - Pandey, Shivendra Kumar; Sharma, Dheeraj
Abstract : Purpose: The purpose of this paper is to examine the sunk-time fallacy in the context of simultaneous variations of time and money when financial expenditures are recoverable. The study compares a recoverable monetary scenario with conditions where money is either not spent or spent, but purchase and payment are decoupled. Design/methodology/approach: A sample of 184 participants was utilised in three experiments. A randomised design was used, and experimental manipulations were achieved using the vignette method. Findings: The results indicate that consumers are susceptible to sunk-time fallacy. Specifically, results suggest that there is no significant difference in sunk cost fallacy when a consumer spends only time vs when a consumer spends money and time both but money can be recovered. The sunk-time fallacy did not occur in credit card purchases. The sunk-time fallacy did not happen in temporal investments of less than a week but appeared in the temporal investments of two weeks. Research limitations/implications: The study indicates that sunk-time fallacy occurs after a minimum threshold of time is spent on a particular activity. Practical implications: Online retailers may vary the delivery period of ordered merchandise to reduce product returns. Online retailers may not deliver the merchandise too early to take advantage of the sunk-time fallacy. Bestseller products should be quickly delivered as there are lesser chances of product return. On the other hand, new products or products with mixed consumer reviews should be provided preferably with a time lag beyond a week. Managers should incentivise payments through debit card/net banking and cash-on-delivery to reduce returns by using sunk-time fallacy. Originality/value: The study is perhaps the first one to study the sunk-time fallacy in a simultaneous variation of time and money where monetary costs can be recovered fully.